THE INFLUENCE OF EARNING MANAGEMENT, OPERATIONAL COSTS AND TAX PLANNING ON INCOME TAX PAYABLE - Hamida Hunein; Muhamad Arief Hidayat; Listya Sugiyarti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze how the variables of Earning Management, Operating Costs, and Tax Planning affect Income Tax Payable in Energy sector companies listed on the Indonesia Stock Exchange. The research method carried out is a quantitative research method with a panel data regression technique and the type of data used in this study is secondary data. In this study, to obtain a sample, special criteria are needed, so the purposive sampling method is used. This study has a population of 87 companies and obtained 19 company samples and the results of observations include 95 research data for five years in the 2019-2023 period. The analysis used in this study was using panel data regression with EViews 13 software. The results of the model selection test in this study show that the best model to use is the Fixed Effect Model (FEM). This study obtained results, namely simultaneously, Earning Management, Operational Costs, and Tax Planning have an effect on Income Tax of Accounts Receivable and partially, Earning Management has no effect on Income Tax of Accounts Receivable, Operational Costs affect Income Tax of Accounts Receivable, Tax Planning has no effect on Income Tax of Accounts Receivable.